Epidemiology and clinical features of maternal sepsis: A retrospective study of whole pregnancy period. Issue 40 (7th October 2022) - Zhong, Xuan; Lin, Rongfeng; Zhang, Wenni; Huang, Shan; Luo, Yiping; Wang, Ding
Abstract : Maternal sepsis results in poor outcomes such as fetal or maternal death. The incidence and mortality rates of maternal sepsis vary in different places because of differences in economic development, race and medical conditions. Identifying the clinical features and determining possible mechanisms for avoiding morbidity and preventing poor outcomes would benefit committed patients. Therefore, this was an epidemiological study at a maternity transfer center in Southeast China that aimed to identify local disease features of maternal sepsis. To investigate the incidence and risk factors associated with maternal sepsis and its progression to severe sepsis in a large population-based birth cohort. This local epidemiological study was conducted in at a tertiary care center in Guangzhou, China, from 2015 to 2019. A total of 74, 969 pregnant women experiencing childbirth were included in this study; Of these, 74 patients with maternal sepsis were diagnosed according to the sepsis criterion, and 118 patients without sepsis in the same period were selected randomly as the control group to study possible reasons for postpartum sepsis. This retrospective analysis covered the entire period from the first trimester to puerperium. Clinical data were collected using the hospital's electronic medical record system. Multivariate logistic regression was used to analyze risk factors for maternal sepsis. The incidences of maternal sepsis, the maternal mortality, and the fetal mortality were 0.099%, 0.004%, and 0.007%, respectively. Septic shock was associated with a higher severity of illness. All poor outcomes (maternal or fetal death) occurred during pregnancy. Postpartum sepsis had the longest onset period, and was associated with premature rupture of fetal membranes and preeclampsia. Sepsis is an important cause of both maternal and fetal mortality. Herein, we describe an epidemiological study that evaluated the incidence, development, and prognosis of local maternal sepsis. Furthermore, the characteristics of maternal sepsis are likely due to unknown pathological mechanisms, and patients would benefit from identifying more effective treatments for maternal sepsis.